2019
DOI: 10.1002/adfm.201900075
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Vascularized Liver Chip for Cross‐Validation of Disease Treatment with Animal Model

Abstract: Artificial liver models have been extensively developed for pathological modeling and toxicological studies. However, the prediction of existing in vitro liver models rarely corresponds to what is consequently observed in vivo owing to the structural and functional complexity of the liver. Here, a new liver model designed to enable the implantation and maintenance of liver buds in perfusable 3D hydrogels where a microvascular network develops within a 200 µm diffusion limit is developed. This system replicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…The microchannel size was set up first to mimic the diameter range of capillary (5-10 µm), a small blood vessel 38 . Second, our previous studies proved that this diameter range of pores promoted micro blood vessel formation into the polymer's scaffolds when implanted subcutaneously in mice 39 while also accelerating the histological and functional recoveries of post hepatectomy liver via implantation of the same vascular network hydrogel that also contained minced pieces of autologous liver tissue in rabbits 31 . Lastly, a study reported that~15 µm diameter pores induced M2 polarization and angiogenic activities 40 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The microchannel size was set up first to mimic the diameter range of capillary (5-10 µm), a small blood vessel 38 . Second, our previous studies proved that this diameter range of pores promoted micro blood vessel formation into the polymer's scaffolds when implanted subcutaneously in mice 39 while also accelerating the histological and functional recoveries of post hepatectomy liver via implantation of the same vascular network hydrogel that also contained minced pieces of autologous liver tissue in rabbits 31 . Lastly, a study reported that~15 µm diameter pores induced M2 polarization and angiogenic activities 40 .…”
Section: Discussionmentioning
confidence: 93%
“…1 and 2). In our previous study, the washing process enabled complete removal of PNIPAM fibers throughout the channel gel when analyzed by digital imaging and high-performance liquid chromatography (HPLC) 31 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the genetic variation and the difficulty in developing global standard protocols for animal studies [28] have made researchers look for alternatives. Recently, vascularized microfluidic LOCs have revolutionized the in vitro tissue and organ models, and resulted in the development of vascularized models of, retina [29], skin [30], hair [31], bone [32], thyroid [33], heart [34], lungs, [35], kidney [36], pancreas [37], liver [38], and intestine [39], respectively. A vascularized body-on-chip, linking eight different organs, including the brain and a BBB, transforming the future drug screening technology, was also reported [40].…”
mentioning
confidence: 99%
“…The human-like perfusability, dynamic microenvironment, and the ability to carry out robust, rapid and reproducible assays in a controlled operational condition, with high throughput screening readouts, have made the above devices a super-tool to screen angiogenic drugs [41]. Some of the above devices were already evaluated for drug screening [32,34,36,38,40], and a few studied the effect of NPs [35,41] and NMs [39].Microfluidic technology has also been used to model brain vasculogenesis/angiogenesis [42][43][44][45][46], BBB [2,42,[47][48][49][50][51][52][53], brain tissues [54,55], and brain angiogenesis-related cellular events such as inflammation [47,50], cell migration [56], cell-cell interactions [57], etc., see Table 2. In addition, specific conditions, involving pathological-angiogenesis, such as brain tumors [46,[54][55][56]58], ischemic strokes [59], and neurodegenerative disorders including Alzheimer's disease (AD) [60], Parkinson's disease (PD) [61], and Huntington's disease (HD) [62], could also be created on-chip.In addition to this, LOCs have been developed for studying the biocompatibility, cellular uptake and transport of NMs [2,27], many of them focusing on brain angiogenesis [2,45,…”
mentioning
confidence: 99%